Anthropometry and Occlusion: A Cross-Sectional Insight into Finger Measurements and Vertical Dimension of Occlusion in Madhya Pradesh - Megha Patil; Mukesh Soni; Alka Gupta; Harsh Chansoria; Harshita Sachdev; P Suthakar (Journal of Pharmacy and Bioallied Sciences)
Introduction: Anthropometry plays a crucial role in forensics and clinical medicine. This study examines the relationship between the vertical dimension of occlusion (OVD) and finger measurements in the Madhya Pradesh population, with a focus on gender differences. Materials and Methods: A cross-sectional study was conducted on 200 participants (100 males, 100 females), aged 25-45, measured OVD and finger lengths (thumb, index, little) were measured using a digital caliper. Pearson’s Correlation Coefficient was used to assess the relationships between OVD and finger measurements. Results: Males had higher OVD and longer finger lengths compared to females. Strong correlations were found between OVD and the thumb, little fingers, while the correlation with the index finger correlation was weaker. Conclusion: Finger measurements may serve as a non-invasive method for OVD estimation, relevant to dental prosthetics and forensics. Further research is recommended.